Smart Cities and Mobility Stations. Lessons learned from the Smarter Together in Vienna and Munich. - Maciel Costa da Silva, Luiza (My University, 2020)
Smart mobility strategies, such as shared mobility and mobility stations, represent some of the solutions to promote changes in travel behavior. Despite its beneficial impacts, however, the implementation of such infrastructure is criticized for not contributing to current urban issues, as well as often disregarding knowledge about urban space and its functioning. In this context, the Smarter Together, a joint research and innovation project funded through the European Union program H2020, was implemented. The project selected three lighthouse cities to test and upscale innovative solutions: Vienna, Munich, and Lyon. This thesis presents the main characteristics of the mobility stations systems implemented in Vienna and Munich in the scope of the project Smarter Together. Its main goal is to share what can be learned from their experiences while approaching critically the concept of smart cities. This thesis identifies important aspects to take into account when planning, implementing, and operating mobility stations, and provides an understanding of smart cities and smart mobility that goes beyond the adoption of technology. Several methods were combined for the development of this thesis, such as quantitative secondary data, observational studies, application of survey forms, explorative expert interviews, and literature review. This work has demonstrated that the Smarter Together has a cutting-edge scope and contributed greatly to research and innovation, by creating living laboratories to test the application of technology in the urban environment. However, from the perspective of the mobility stations assessment, many caveats were made.
Smart Cities and Mobility Stations. Lessons learned from the Smarter Together in Vienna and Munich.
Keywords: Verkehr; Verkehrspolitik; Verkehrskonzept; Mobilitätsentwicklung; Stadtverkehr; Smart City; Nachhaltige Verkehrsentwicklung; Modellprojekt; Projektbericht; Car-Sharing; E-Mobilität; Fahrradverkehr; E-Bike; Mobilitätsstation; Smart Mobility; Shared Mobility; Bike-Sharing; City Logistik